Mexico Twelve Years After the Implementation of the NAFTA (Análisis Económico, 2024)
Today, twelve years after the North American Free Trade Agreement came into effect; we evaluate Mexico’s major objectives with the ones accomplished within its relationship with the United States and Canada in the context of the Agreement. We carry out a reflexion on the central problems of said relationship: competitivity, growth, employment, prices, and wages; the expected (but not achieved) direct economic effects; what Mexican industry and agriculture took advantage of, or did not, from the Agreement, emphasizing the role of Mexican Government policies. We also consider some issues that need to be incorporated into the Agreement (migration), and renegotiated (environmental matters, and the arbitration of controversies) in order to obtain larger and better benefits from it. Finally, Mexico’s perspectives, in relation to the commercial agreement are expressed in a possible future agenda, and tasks still to be done.